A Comparison between Two Instruments for Assessing Dependency in Daily Activities: Agreement of the Northwick Park Dependency Score with the Functional Independence Measure. (18th November 2012) - Svensson, Siv; Sunnerhagen, Katharina Stibrant
Abstract : Background . There is a need for tools to assess dependency among persons with severe impairments. Objectives . The aim was to compare the Functional Independence Measure (FIM) and the Northwick Park Dependency Score (NPDS), in a sample from in-patient rehabilitation. Material and Methods . Data from 115 persons (20 to 65 years of age) with neurological impairments was gathered. Analyses were made of sensitivity, specificity, positive predictive value, and negative predictive value. Agreement of the scales was assessed with kappa and concordance with Goodman-Kruskal's gamma. Scale structures were explored using the Rank-Transformable Pattern of Agreement (RTPA). Content validation was performed. Results . The sensitivity of the NPDS as compared to FIM varied between 0.53 (feeding) and 1.0 (mobility) and specificity between 0.64 (mobility) and 1.0 (bladder). The positive predictive value varied from 0.62 (mobility) to 1.0 (bladder), and the negative predictive value varied from 0.48 (bowel) to 1.0 (mobility). Agreement between the scales was moderate to good (four items) and excellent (three items). Concordance was good, with a gamma of −.856, an asymptotic error (ase) of .025, and P < .000 . The parallel reliability between the FIM and the NPDS showed a tendency for NPDS to be more sensitive (having more categories) when dependency is high. Conclusion . FIM and NPDS complement each other. NPDS can be used as a measure for severely injured patients who are sensitive when there is a high need of nursing time.